Bibliometric analysis of resilience in stroke from 2000 to 2024 using CiteSpace and VOSviewer - Li, Yaoyao; Soh, Kim Lam; Jing, XiuJuan; Wei, Lili; Rajen Durai, Ruthpackiavathy; Soh, Kim Geok (Frontiers in Psychology, 2025)
ObjectiveThis study aims to conduct a bibliometric analysis of research literature on psychological resilience among stroke survivors published from 2000 to 2024, utilizing VOSviewer and CiteSpace.MethodsThe literature data was sourced from the Web of Science Core Collection database (WoSCC). A total of 424 relevant articles, published between January 1, 2000, and April 30, 2024, were included. To analyze the literature, the software tools CiteSpace and VOSviewer were employed, examining perspectives such as authorship, country of origin, institutions, journals, references, and keywords.ResultsSince 2015, the annual publication output has steadily increased, reaching a peak in 2022 (65 articles). The United States is the most prolific contributor, with Harvard University being the leading institution in this field. Zhang W and Vranceanu A have emerged as the authors with the highest productivity, each boasting five published articles. “Stroke” is the most co-cited journal (204 times) with a high impact factor (IF 2022, 8.4). The most frequently occurring keywords are “stroke,” “resilience,” “depression,” “health,” and “quality of life.” Emerging trends include research on post-stroke cognitive impairment, meta-analyses, population differences, guideline development, and symptom management.ConclusionThis bibliometric study indicates the increased scholarly interest in investigating psychological resilience among persons who have survived a stroke over the last 24 years. The United States and China have emerged as the leading contributors to this study area, with international collaboration on the rise. To enhance this subject, subsequent studies should target refining theoretical frameworks, enhancing assessment instruments, establishing evidence-based guidelines, and developing tailored therapies that increase psychological resilience and holistic well-being for stroke survivors.